Practical methods of plant breeding - Shelley, Wilson George (My University, 1907)
Introduction: The increasing interest in plant-breeding is one of the most striking characteristics of modern agricultural conditions. Only a few years ago it was thought that almost any kind of seed would do to sow. Most of the selection, or breeding, that was done was of a haphazard, very unscientific nature. It was scarcely realized that any but Luther Burbank and a few other geniuses could carry on careful, systematic breeding of any value. Few were enough interested to even think of it. Now all is changed. The country, especially in the corn belt, is traversed by special trains carrying lecturers who inform the farmers of the best methods of improving their crops. Scientific men all over this and other countries are studying the principles which underlie the breeding of plants. They are striving to discover the best methods of applying these principles in the field. Careful breeding of animals has been in progress for many years, and yet many things are obscure or unknown about it. It is, then, no great wonder that so little is certainly known concerning plant-breeding. Yet even our meager knowledge of principles and proper methods is of great economic value. A small increase in yield per plant or per acre will in the aggregate of the entire country amount to astonishing figures in the case of our staple crops. When we remember that it is only the marginal fraction of the crop which furnishes the profit to the grower---the rest being used to cover expenses---then it is that we realize the advantage to him who has a variety which, from its inherent productiveness, yields more than the average, be it only one or two bushels per acre. A small increase of this kind would often double a farmer’s actual profit.
Citation: Shelley, Wilson George. Practical methods of plant breeding. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Plant Breeding; Methods of Plant Breeding; Plant Maintenance; Theses